Vers une gestion individualisée et externalisée de la difficulté scolaire au Québec - Marjorie Vidal; Marianne St-Onge (Les éditions de la Maison des sciences de l'Homme, 2020)
The aim of this article is to understand how some school practices for pupils in vulnerable situations are based on the same logic as that which led to the marginalisation of these pupils in the first place. It is based on a case study that took place over a period of three and a half years in a high school located in a disadvantaged and multi-ethnic area in Montreal (Québec). Based on the concept of school form (Vincent, 1980), we will present some remedial practices, which are part of an individualised and externalised management of school difficulties and could lead to strengthen the alignment between school intervention and management practices.